Potassium and ion beam induced electron accumulation in InN - Colakerol, L.; Piper, L. F. J.; Fedorov, A.; Chen, T.; Moustakas, T. D.; Smith, K. E. (Elsevier Science Bv, 2015)
We present angle resolved photoemission study of quantized electron accumulation subbands obtained from both clean and potassium deposited InN(000 (1) over bar) surfaces. Shifting of the quantized accumulation states toward higher binding energies upon low energy N-2(+) ion bombardment or a small amount of potassium adsorption is explained by the modification of the In-adlayer induced surface states. N-2(+) ion bombardment leads to a higher density of donor-type surface states by creating nitrogen vacancies near the surface. On the other hand, a small amount of K adsorbates initially donate their free electron to InN and result in more pronounced downward band bending. Eventually, further K adsorption leads to passivation of surface states and reduction of the surface electron accumulation. With the increase of the electron density, enhanced many-body interactions of electrons within the electron accumulation layer are observed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Angle resolved photoemission; Alkali-metal; Charge accumulation; Molecular beam epitaxy; InN surface